Mıdlıne Devıatıons And Treatments - M. Serdar Toroğlu (Galenos Yayinevi, 2000)
Treatment of midline deviation should be started with clinical diagnosis. Clinical patient examination and diagnostic records, such as posterior-anterior radiographs, submen-tovertex radiographs and panoramic radiographs, compose the diagnostic methods. Several intra-arch and inter-arch mechanics can be used as well as multidisciplinary modalities consisting of orthognatic surgery in the treatment of midline deviation. Paying less attention to the treatment of midline deviation at the initial phase would cause ideal treatment of the case impossible. Achieving symmetrical skeletal and dental relationships with functional occlusion should be the aim. In this article, etiology, diagnosis and treatment of the midline deviations are discussed.